Ocean acidification reduces transfer of essential biomolecules in a natural plankton community - Bermúdez, J. Rafael (Sci Rep, 2016)
Ocean acidification (OA), a process of increasing seawater acidity caused by the uptake of anthropogenic carbon dioxide (CO(2)) by the ocean, is expected to change surface ocean pH to levels unprecedented for millions of years, affecting marine food web structures and trophic interactions. Using an in situ mesocosm approach we investigated effects of OA on community composition and trophic transfer of essential fatty acids (FA) in a natural plankton assemblage. Elevated pCO(2) favored the smallest phytoplankton size class in terms of biomass, primarily picoeukaryotes, at the expense of chlorophyta and haptophyta in the nano-plankton size range. This shift in community composition and size structure was accompanied by a decline in the proportion of polyunsaturated FA (PUFA) to total FA content in the nano- and picophytoplankton size fractions. This decline was mirrored in a continuing reduction in the relative PUFA content of the dominant copepod, Calanus finmarchicus, which primarily fed on the nano-size class. Our results demonstrate that a shift in phytoplankton community composition and biochemical composition in response to rising CO(2) can affect the transfer of essential compounds to higher trophic levels, which rely on their prey as a source for essential macromolecules.